Genetics of muscle stiffness, muscle elasticity and explosive strength - Maciejewska-Skrendo, A.; Leznicka, K.; Leonska-Duniec, A.; Wilk, M.; Filip, A.; Cieszczyk, P.; Sawczuk, M. (Journal of Human Kinetics, 2020)
Muscle stiffness, muscle elasticity and explosive strength are the main components of athletes` performance and they show a sex-based as well as ethnicity variation. Muscle stiffness is thought to be one of the risk factors associated with sports injuries and is less common in females than in males. These observations may be explained by circulating levels of sex hormones and their specific receptors. It has been shown that higher levels of estrogen are associated with lower muscle stiffness responsible for suppression of collagen synthesis. It is thought that these properties, at least in part, depend on genetic factors. Particularly, the gene encoding estrogen receptor 1 (ESR1) is one of the candidates that may be associated with muscle stiffness. Muscle elasticity increases with aging and there is evidence suggesting that titin (encoded by the TTN gene), a protein that is expressed in cardiac and skeletal muscles, is one of the factors responsible for elastic properties of the muscles. Mutations in the TTN gene result in some types of muscular dystrophy or cardiomyopathy. In this context, TTN may be regarded as a promising candidate for studying the elastic properties of muscles in athletes. The physiological background of explosive strength depends not only on the muscle architecture and muscle fiber composition, but also on the central nervous system and functionality of neuromuscular units. These properties are, at least partly, genetically determined. In this context, the ACTN3 gene code for a-actinin 3 has been widely researched.